Implementasi PSAK 207 dalam Pelaporan Arus Kas (Cash Flow) pada Perusahaan Telkom Indonesia, Tbk (Persero) Tbk Tahun 2022 - Ruben Suherman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
PSAK 207 in Cash Flow reporting is an accounting standard that regulates cash flow reporting. This standard introduces direct methods and indirect methods. Although the direct method approach requires adjusting net income with elements that do not involve cash flow, the direct method requires reporting gross cash flow from operating activities. The aim of this research is to examine how PT. Telkom Indonesia has implemented PSAK 207 in cash flow reporting. The accounting standard PSAK 207 regulates cash flow reporting, which is critical to providing accurate and timely financial information to stakeholders. This research investigates how the Telkom company applies PSAK 207 in presenting their cash flow reports using a qualitative methodology that includes document analysis and interviews. The results of this research will provide an understanding of the challenges and benefits faced by companies in implementing this standard.